2013
DOI: 10.7196/sajs.1665
|View full text |Cite
|
Sign up to set email alerts
|

Base deficit as an early marker of coagulopathy in trauma

Abstract: BD but not lactate correlates with the development of the coagulopathy of trauma. The ISS showed a significant correlation with coagulation disturbances, and the combination of hypoperfusion and coagulopathy was associated with a significant increase in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…Accepted and validated markers include anion gap, serum lactate and base excess which are readily available by venous or arterial draws. Lactate has been shown to be correlated to the amount of carbon dioxide generated during hemorrhagic shock 22 . Base excess (derived from an equation that includes HCO3 and pH) is an estimation of the amount of bicarbonate produced in the blood in that it is the amount of base or acid required to return 1 liter of whole blood to a pH 7.4 and is impacted by factors that raise or lower the pH (such as high anion gap metabolic acidosis which can be caused by a lactic acidosis).…”
Section: Discussionmentioning
confidence: 99%
“…Accepted and validated markers include anion gap, serum lactate and base excess which are readily available by venous or arterial draws. Lactate has been shown to be correlated to the amount of carbon dioxide generated during hemorrhagic shock 22 . Base excess (derived from an equation that includes HCO3 and pH) is an estimation of the amount of bicarbonate produced in the blood in that it is the amount of base or acid required to return 1 liter of whole blood to a pH 7.4 and is impacted by factors that raise or lower the pH (such as high anion gap metabolic acidosis which can be caused by a lactic acidosis).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have validated the usefulness of blood lactate and BD in trauma patients as markers of injury severity [25–28], as endpoints of resuscitation [20, 29], as a means to monitor treatment efficacy [3032], and as predictors of outcome [33–36]. Despite indicating the severity of hypoperfusion [37, 38], measurement of lactate alone may not fully encompass the extent of the underlying metabolic acidosis [39]. On the contrary, BD can quantify the extent of both anaerobic and aerobic acidosis and may be a better clinical indicator for the global assessment of the metabolic acid-base status [32, 3941].…”
Section: Introductionmentioning
confidence: 99%
“…Despite indicating the severity of hypoperfusion [37, 38], measurement of lactate alone may not fully encompass the extent of the underlying metabolic acidosis [39]. On the contrary, BD can quantify the extent of both anaerobic and aerobic acidosis and may be a better clinical indicator for the global assessment of the metabolic acid-base status [32, 3941]. In addition, prior studies have suggested that elevated arterial BD (≥4 mEq/L) upon admission after injury can be a reliable predictor of multiple organ dysfunction, morbidity, and mortality in moderately/severely injured patients [21, 34, 36, 4244].…”
Section: Introductionmentioning
confidence: 99%
“…ATC occurs in approximately 25% of trauma patients 5 and may manifest as abnormal coagulation within 30 minutes following traumatic wounding, 6 a time span and condition not associated with significant fibrinogen consumption and before iatrogenic hemodilution caused by resuscitative efforts. 7 The international normalized ratio (INR), which strongly correlates with a lack of adequate tissue blood flow in surgical and trauma patients, 8 is the most commonly used indicator of ATC. However, information provided by the INR, while more sensitive to coagulation factor activity and thrombin generation, is correlative at best and does not reflect platelet function or red blood cell (RBC) influence.…”
mentioning
confidence: 99%